Pengelolaan Pengendalian Biaya Kualitas Terhadap Volume Penjualan melalui Strategi Akuntansi Manajemen - Wiwit Lusiana; Agus Pawitra Widya; Maria Yovita R Pandin (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
In order to make a profit, companies need to manage marketing costs properly, this can be done by using a management accounting information system. This study investigates the effect of product quality and promotion on management accounting information systems. It also investigates whether the management accounting information system is a good mediator. This study conducted a survey of consumers at UD Tiga Saudara Surabaya. Using purposive sampling method with the sample criteria being consumers who have had at least 1 transaction, 97 respondents were obtained. The data was then analyzed using Structural Equation Modeling. The findings show that product quality and promotion contribute positively to the management accounting information system. The study also proved that the management accounting information system mediates the relationship of product quality and promotion to employee sales volume. This study contributes to marketing management theory by using the framework of management accounting information system and sales volume.